Enabling efficient and effective data extraction and data labeling - Zhang, Y (2022)
History has left us with many wonderful visualizations. Historical visualizations capture valuable historical statistics. The original datasets that generate historical visualizations are useful to humanities and social science scholars but are often lost. This thesis starts with the problem of extracting such datasets from historical visualizations. It is impractical to expect purely automatic solutions for data extraction, as historical visualizations feature diverse designs, contain image defects, and the data extraction has low error tolerance. Meanwhile, manual extraction is laborious. It calls for efficient and effective solutions.